Volatility transmissions between renminbi and Asia-Pacific on-shore and off-shore U.S. dollar futures - Roberta Colavecchio; Michael Funke (Bank of Finland, Institute for Economies in Transition (BOFIT), 2006)
This paper uses multivariate GARCH techniques to study volatility spillovers between the Chinese non-deliverable forward market and seven of its Asia-Pacific counterparts over the period January 1998 to March 2005.To account for the time-variability of conditional correlation, a dynamic correlation structure is included in the volatility model specification.The empirical results demonstrate that the renminbi non-deliverable forward (NDF) has been a driver of various Asian currency markets but that such co-movements exhibit a substantial degree of heterogeneity.As to the determinants of the magnitude of these comovements, we test the relevance of potential factors and find that it is the degree of real and financial integration, in particular, that exerts the largest influence on volatility transmission.
URN:NBN:fi:bof-201408072229
Keywords: C22; F31; F36; 330; China; renminbi; Asia; forward exchange rates; non-deliverable forward market; multivariate GARCH models